Disentangling a taxonomic nightmare: a revision of the Australian, Indomalayan and Pacific species of Altica Geoffroy, 1762 (Coleoptera: Chrysomelidae: Galerucinae) - Reid, C. A. M.; Beatson, M. (Zootaxa, 2015)
The genus Altica Geoffroy, 1762, is revised for Australia, the west Pacific region and the Indomalayan Archipelago, with 6 valid species: A. aenea (Olivier, 1808); A. birmanensis (Jacoby, 1896); A. caerulea (Olivier, 1791); A. corrusca (Erichson, 1842); A. cyanea Weber, 1801; A. gravida (Blackburn, 1896). The following new synonymy is recognised, in original combinations, senior synonym first: Galeruca aenea Olivier = Haltica ignea Blackburn, 1889, syn. nov., = Haltica bicolora Jacoby, 1904, syn. nov., = Altica jussiaeae Gressitt, 1955, syn. nov.; Galeruca caerulea Olivier = Haltica elongata Jacoby, 1884, syn. nov., = Altica brevicosta Weise, 1922; Haltica corrusca Erichson = Haltica pagana Blackburn, 1896, syn. nov.; Haltica birmanensis Jacoby = Haltica indica Shukla, 1960, syn. nov. Altica brevicosta and A. birmanensis are removed from synonymy with A. cyanea and A. indica is removed from synonymy with A. caerulea. The Altica caerulea of Maulik and subsequent authors (not Olivier) is a misidentification of two species, correctly named A. cyanea and A. birmanensis. The Altica cyanea of Maulik and subsequent authors (not Weber) is a misidentification, correctly named A. aenea. Altica bicosta Shukla, 1960, is removed from synonymy with A. brevicosta and regarded as a valid species. Altica splendida Olivier, 1808, and Haltica ferruginis Blackburn, 1889, are transferred to Sutrea Baly, 1876, as S. splendida (comb. nov.) and S. ferruginis (comb. nov.). The type species of Sutrea is designated as S. elegans Baly, 1876. Altica albicornis Medvedev, 2004, is transferred to Phygasia Dejean, 1836, as P. albicornis (comb. nov.). Lectotypes are designated for A. australis, A. birmanensis, A. caerulea, A. cyanea, A. elongata, A. ignea and A. pagana. A neotype is designated for A. aenea. Altica caerulea is newly recorded from Australia and A. cyanea is removed from the Australian fauna. Altica corrusca and A. gravida are endemic to Australia; all published records of these species from outside Australia refer to the widespread Asian-Pacific species A. aenea. The single record of the European Altica oleracea (L., 1758) from New Caledonia is regarded as a label error and this species removed from the Pacific fauna. A key, based primarily on genitalic structures, is provided for the six regional species and all are redescribed. Host plant records are reviewed: A. corrusca is a minor agricultural pest; A. aenea, A. caerulea and A. cyanea may be useful for biocontrol of weeds.